"Always a Preemie": Maternal Experiences Parenting a Very Preterm Infant into Toddlerhood. Issue 2 (June 2022) - Quist, Megan; Julian, Megan M.; Meerkov, Meera; Pesch, Megan H.
This study sought to qualitatively describe themes in maternal narratives around parenting a former very or extremely preterm infant from the neonatal intensive care unit (NICU) into toddlerhood. Mothers (N = 14) of preterm infants ≤28 weeks gestation, now aged 2 to 4 years, completed a semi-structured interview; transcripts were qualitatively analyzed. Five themes of mothers' experiences were identified: (a) anxiety and trauma related to birth and NICU stay; (b) the importance of clear communication with medical providers; (c) mothers' need for and difficulty accessing self-care opportunities or services; (d) challenges of transitioning home; and (e) mothers, continued view of their toddlers as vulnerable and "always a preemie." Most (11/14) mothers reported depressive symptoms in the clinically significant range. Results of this study highlight the potential hardships and lasting maternal mental health effects of raising a former very or extremely preterm infant, and the need for supports in the NICU, at discharge and longitudinally.